2010
DOI: 10.1051/0004-6361/200913081
|View full text |Cite
|
Sign up to set email alerts
|

A precise measurement of the solar differential rotation by tracing small bright coronal structures in SOHO-EIT images

Abstract: Aims. We precisely determine the solar rotation velocity during most of the 23rd solar cycle, in the years 1998−2006. We measure the solar differential rotation by tracing small bright coronal structures (SBCS) in SOHO-EIT images. Methods. The 28.4 nm EIT channel was used and positions of more than 55 000 structures were measured applying an interactive and improved automatic method of data reduction. Results. We achieve the closest representation of the observational data when all three solar differential rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Although, this effect is probably negligible for the solar rotation, it might create problems for derived quantities such as rotation velocity residuals or Reynolds stress. Brajša et al (2001) and Wöhl et al (2010) adopted a different, two-step approach where they first applied the fixed filter, calculated the solar rotation profile, and then eliminated all measurements which differed by more than 2 • day −1 from the calculated profile. Finally, the new profile was calculated with a truncated dataset.…”
Section: Data and Reduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, this effect is probably negligible for the solar rotation, it might create problems for derived quantities such as rotation velocity residuals or Reynolds stress. Brajša et al (2001) and Wöhl et al (2010) adopted a different, two-step approach where they first applied the fixed filter, calculated the solar rotation profile, and then eliminated all measurements which differed by more than 2 • day −1 from the calculated profile. Finally, the new profile was calculated with a truncated dataset.…”
Section: Data and Reduction Methodsmentioning
confidence: 99%
“…Coronal bright points (CBPs) have also been used very frequently by using the data obtained by different satellites. For example, Brajša et al (2001Brajša et al ( , 2002bBrajša et al ( , 2004, Vršnak et al (2003), Wöhl et al (2010) used SOHO/EIT data, Hara (2009) analysed Yohkoh/SXT measurements, while Kariyappa (2008) used both Yohkoh and Hinode data. Recently, Sudar et al (2015) have used SDO/AIA measurements in the 19.3 nm channel.…”
Section: Introductionmentioning
confidence: 99%
“…The secular deceleration of solar rotation was suggested by Brajša et al (2006) and Li et al (2011), while a secular acceleration trend was found by Heristchi & Mouradian (2009). A north-south asymmetry in solar rotation has been reported by many authors Balthasar et al 1986;Antonucci et al 1990;Rybák 1994Rybák , 2000Brajša et al 1997Brajša et al , 2000Javaraiah 2003;Georgieva et al 2005;Mursula & Hiltula 2004;Gigolashvili et al 2007;Zaatri et al 2009;Wöhl et al 2010), but there is so far no agreement on which of the two hemispheres is rotating faster, or how the difference between the hemispheric rotation rates is changing in time.…”
Section: Introductionmentioning
confidence: 91%
“…Some authors have shown that there is an almost rigid corona in soft X‐ray and UV rays, or a shallower rotation profile of the corona that varies with latitudes unlike at the lower atmosphere (Timothy, Krieger & Vaiana 1975; Weber, Alexander & Acton 1997; Weber et al 1999; Chandra, Vats & Iyer 2010; Chandra & Vats 2011; Vats & Chandra 2011). However, others have obtained contrasting results (Brajs̆a et al 2002, 2004; Karachik et al 2006; Zaatri et al 2009; Wöhl et al 2010). Vats et al (1998a,b) have studied the rotational modulation of the solar radio flux, and they found that the solar corona rotates slightly faster than the photospheric features.…”
Section: Introductionmentioning
confidence: 98%